Babaeng Frontliner at COVID-19 sa Pilipinas: Batayan para sa Isang Epektibong Tugon sa Pandemya na Nakatuon sa Gender (Female Frontliners and COVID-19 in the Philippines: Basis for a Gender-Responsive Pandemic Response) - Fernando, Arianne Nicole (Social Sciences and Development Review, 2025)
While the mortality rates for men are higher, the socioeconomic impact of the COVID-19 pandemic hit women differently. This qualitative study examines the experiences of eight Filipina frontliners who continued to work during the General Community Quarantine in Metro Manila. Respondents were selected through purposive sampling. The primary data collection method was in depth interview. Phenomenological study was utilized for data analysis. The research resulted in three major themes which emerged out of the experiences shared by the female frontliners (1) there exists a problem in safety and transportation among female frontliners; (2) stress develops from a high-risk work task; (3) coping strategies are utilized to manage daily stressors. Paying attention to concerns of female frontliners can potentially improve preventive practices and positive behaviors in combating the pandemic. There should be a gender lens on the response to COVID-19 to ensure that the unique needs women are addressed not just in the Philippines but in the whole world. Frontline female responders must be guaranteed protection safe working conditions support and fair compensation that answers their needs. Also, there is a necessity for sex and age disaggregated data to further understand how this crisis is impacting women and men differently and to support the data collected from the respondents in implementing gender sensitive an effective response to pandemics.
Keywords: female frontliners; gender; qualitative; Philippines; COVID19; pandemic